In pursuit of the perfect portfolio the stories, voices, and key insights of the pioneers who shaped the way we invest - Lo, Andrew W. (Andrew Wen-Chuan) (Princeton University Press, 2021)
Is there an ideal portfolio of investment assets, one that perfectly balances risk and reward? In Pursuit of the Perfect Portfolio examines this question by profiling and interviewing ten of the most prominent figures in the finance world: Jack Bogle, Charley Ellis, Gene Fama, Marty Liebowitz, Harry Markowitz, Bob Merton, Myron Scholes, Bill Sharpe, Bob Shiller, and Jeremy Siegel. We learn about the personal and intellectual journeys of these luminaries, which include six Nobel Laureates and a trailblazer in mutual funds, and their most innovative contributions. In the process, we come to understand how the science of modern investing came to be. Each of these finance greats discusses their idea of a perfect portfolio, offering invaluable insights to today's investors.